Emergency remote teaching and learning in simultaneous interpreting: Capturing experiences of teachers and students - Alex Krouglov (Peoples' Friendship University of Russia (RUDN University), 2021)
The article covers the transfer to emergency remote teaching and learning in Simultaneous Interpreting (SI) during the Covid-19 pandemic and the lockdown in early 2020. The study aims to establish some approaches as to how the emergency move to online training was conducted, what we can learn from this experience and what were the main challenges. The article presents and analyses the findings of the survey of teaching staff and students in seven universities in Europe and Australia. Twelve interviews were conducted remotely with selected members of teaching staff and students. The study confirms that universities were able to complete their modules in Simultaneous Interpreting by making arrangements for a smooth transfer to remote training in synchronous and asynchronous modes. The transfer and emergency remote teaching and learning mostly depended on the prior experience of teaching teams in delivering online workshops and webinars and their close engagement with students. The role of course or module leader has been outlined as key to providing leadership during the transfer to emergency arrangements during lockdown. One of the conclusions of this study addresses the need for teaching remote interpreting within university Interpreting or Translation and Interpreting courses in view of the current situation with the Covid-19 pandemic and possible new requirements in the future.